PROSEDUR PEMERIKSAAN KNEE JOINT DEXTRA PADA KLINIS OSTEOARTHRITIS DI ISTALASI RADIOLOGI RSUD ARIFIN ACHMAD PEKANBARU - Mahfadel Apari (LPPM Universitas Awal Bros, 2024)
Procedure for radiographic examination of osteoarthritis in the literature by Lampignano and Kendrick (2018), Bilateral AP Weight Bearing projection is used. Meanwhile, for examinations at the Radiology Installation of ARIFIN ACHMAD Regional Hospital, AP projection in the vertical beam direction was used straight and lateral on one side. The aim of this research is to find out the procedure radiographic examination of the knee joint with clinical osteoarthritis, the reason for using the AP / Lat erect projection on one side, as well as the reason for using a perpendicular ray direction in the projection Antero Posterior (AP). This research is qualitative research with a case study approach. Data collection was carried out by means of observation, interviews and documentation. From the results Research shows that radiographic examination of the knee joint is associated with clinical osteoarthritis requires no preparation. Image processing is carried out using computed radiography. Projection AP supine and lateral on one side are used because they can provide information on bone structure, osteophytes, and narrowing of joint spaces, and provides comfort to patient. In the supine position there is no pressure on the patient's body weight, resulting in narrowing Joint space is less than optimal in establishing a diagnosis of osteoarthritis. Use of vertical beam direction straight on the Antero Posterior (AP) projection, the results of the radiograph can still be seen bone structure, osteophytes, and joint space narrowing in diagnosing osteoarthritis